Tenuous silence : urban anxieties and the mitigation of noise in Singapore, 1870 - 1939 - Teo, Grace Jie Ying (Nanyang Technological University, 2020)
Legislative regulations, law enforcement, and judicial processes formed part of the solution dedicated to the ‘sanitizing’ of Asian music in public streets and residential neighbourhoods in Singapore between the 1870s to 1890s. Demands for government intervention to maintain law and order since the mid-nineteenth century culminated in early drafts of police laws governing Asian street and stationary music in the 1870s. In 1895, grievances towards the disturbances to sleep and quiet living conditions by Asian music in wayangs or private musical performances reached a crescendo in the English-language noise nuisance discourse in the press. Judging by the sentiment of the European community, who heard the sounds of Asian music as unfamiliar and unrelenting noise, the demands for more stringent laws and tighter regulations was both an appeal to the colonial obligation to rule and a deeper reflection of racial encroachment fears in the neighbourhood. Using a selection of newspaper commentary and reports on legal cases, the thesis peeks beyond official discourse and legislative wording to examine its actual practice with its intended consequences and unprecedented limitations. While the playing of Asian music in public streets was subjected to licensing requirements under the 1870s regulations, the ease of suppression of unlicensed public noise contrasted the state of the law that was seemingly ill-equipped to address private noise. Due to the public jurisdiction of nuisance abatement laws, the reluctance to be seen as overstepping on religious freedom and Asian liberties in legislative and judicial matters, and an absent collective front against neighbourhood noises, the thesis argues that individual complainants faced mounting challenges in seeking redress for private or domestic noise nuisance well into the twentieth century. By demonstrating that the law was not immediately advantageous to European complainants of noise, the thesis suggests that the practice and enforcement of the law in music regulation nuances the balance of power in the colonial setting.